Conductivity studies of poly(ethylene oxide)(PEO)/poly(vinyl alcohol) (PVA) blend gel polymer electrolytes for dye-sensitized solar cells - Tiong, T.S.; Buraidah, M.H.; Teo, L.P.; Arof, Abdul Kariem (Springer Verlag, 2016)
Poly(ethylene oxide)(PEO)–poly(vinyl alcohol) (PVA) blend-based gel polymer electrolytes (GPEs) have been prepared by blending equal weights of PEO and PVA in ethylene carbonate (EC), dimethyl sulfoxide (DMSO), tetrabutylammonium iodide (TBAI), and iodine crystals (I2). The conductivity, diffusion coefficient, number density, and ion mobility of the electrolytes have been calculated from the impedance data obtained from electrochemical impedance spectroscopy (EIS) measurements. The GPE with the composition of 7.02 wt%, PVA, 7.02 wt% PEO, 30.11 wt% ethylene carbonate (EC), 30.11 wt% DMSO, 24.08 wt% TBAI and 1.66 wt% I2 exhibits the highest conductivity of 5.5 mS cm−1 at room temperature. Dye-sensitized solar cells (DSSCs) with configuration fluorine tin oxide (FTO)/titanium dioxide/N3-dye/GPE/platinum/FTO have been fabricated and tested under the white light of intensity 100 mW cm−2. The DSSC containing the highest conducting GPE exhibits the highest power conversion efficiency, η of 5.36 %.